Fatores associados à gravidade da COVID-19 em gestantes adolescentes brasileiras: estudo de base populacional - Duarte, Brenda Katheryne [UNESP]; Parenti, Ana Beatriz Henrique [UNESP]; Jamas, Milena Temer [UNESP]; Nunes, Hélio Rubens De Carvalho [UNESP]; Parada, Cristina Maria Garcia De Lima [UNESP] (FapUNIFESP (SciELO), 2022)
OBJECTIVE: to identify the factors associated with need for intensive care unit admission of Brazilian pregnant adolescents with COVID-19. METHOD: population-based non-concurrent cohort study using secondary databases. Brazilian pregnant adolescents who had laboratory confirmation of SARS-CoV-2 by RT-PCR, between March 14, 2020 and April 11, 2021 were included in the study. Statistical analysis using the Poisson multiple regression model, estimating the relative risk and respective 95% confidence intervals, with values of p <0.05 considered significant. RESULTS: in total, 282 pregnant women were included in the study, with median age of 17 years, most with brown skin, in the third trimester of pregnancy, and living in urban or peri-urban areas. The intensive care unit admission rate was 14.5%, associated with living in the Southeast region of Brazil (RR=5.03, 95%CI=1.78-14.24, p=0.002), oxygen saturation below 95% (RR=2.62, 95%CI=1.17-5.87, p=0.019), and having some comorbidity (RR=2.05, 95%CI=1.01-4.16, p=0.047). CONCLUSION: the intensive care unit admission rate was high among Brazilian pregnant adolescents and was associated with living in the Southeast region of Brazil, having some comorbidity and/or presenting low oxygen saturation. (1) The ICU admission rate of pregnant adolescents was high: 14.5%. (2) Low oxygen saturation was a predictor of COVID-19 severity. (3) Living in the Southeast region in Brazil increased the risk of ICU admission by five times. (4) Having some comorbidity increased the risk of ICU admission by two times.

OBJETIVO: identificar los factores asociados a la necesidad de hospitalización en unidad de cuidados intensivos en adolescentes brasileñas embarazadas con COVID-19. MÉTODO: estudio de cohorte no concurrente de base poblacional, utilizando bases de datos secundarias. El estudio incluyó adolescentes brasileñas embarazadas que tuvieron confirmación de laboratorio de SARS-CoV-2 por Real Time, entre el 14 de marzo de 2020 y el 11 de abril de 2021. Análisis estadístico realizado por el modelo de regresión múltiple de Poisson, estimándose el riesgo relativo y respectivos intervalos de confianza del 95%, siendo significativos valores de p <0,05. RESULTADOS: se incluyeron en el análisis 282 gestantes, con mediana de edad de 17 años, la mayoría de color de piel parda, en el tercer trimestre del embarazo y residentes en zona urbana o periurbana. La tasa de hospitalización en la unidad de cuidados intensivos fue del 14,5%, asociada a vivir en la región Sudeste (RR=5,03, IC95%=1,78-14,24, p=0,002), tener saturación sanguínea de oxígeno inferior al 95% (RR=2,62, IC95%=1,17-5,87, p=0,019) y tener alguna comorbilidad (RR=2,05, IC95%=1,01-4,16, p=0,047). CONCLUSIÓN: la tasa de hospitalización en cuidados intensivos fue alta entre las adolescentes brasileñas embarazadas y se asoció con vivir en la región Sudeste, tener alguna comorbilidad y/o tener baja saturación de oxígeno.

OBJETIVO: identificar os fatores associados à necessidade de internação em unidade de terapia intensiva em gestantes adolescentes brasileiras com COVID-19. MÉTODO: estudo de coorte não concorrente de base populacional, utilizando banco de dados secundários. Foram incluídas no estudo as gestantes adolescentes brasileiras que possuíam confirmação laboratorial de SARS-CoV-2 por Real Time, entre 14 de março de 2020 e 11 abril de 2021. Análise estatística realizada pelo modelo de regressão múltipla de Poisson, estimando-se o risco relativo e respectivos intervalos de confiança de 95%, sendo significativos valores de p <0,05. RESULTADOS: foram incluídas na análise 282 gestantes, com mediana de idade de 17 anos, a maioria com cor da pele parda, no terceiro trimestre de gestação e residentes em zona urbana ou periurbana. A taxa de internação em unidade de terapia intensiva foi de 14,5%, associando-se a viver na região Sudeste (RR=5,03, IC95%=1,78-14,24, p=0,002), ter saturação de oxigênio inferior a 95% (RR=2,62, IC95%=1,17-5,87, p=0,019) e possuir alguma comorbidade (RR=2,05, IC95%=1,01-4,16, p=0,047). CONCLUSÃO: a taxa de internação em terapia intensiva foi elevada entre gestantes adolescentes brasileiras e associou-se a viver na região Sudeste, possuir alguma comorbidade e/ou apresentar baixa saturação de oxigênio.

(1) A taxa de internação de gestantes adolescentes em UTI foi elevada: 14,5%. (2) A baixa saturação de oxigênio foi um preditor de gravidade da COVID-19. (3) Viver na região Sudeste aumentou em cinco vezes o risco de internação em UTI. (4) Possuir comorbidade aumentou em duas vezes o risco de internação em UTI.
Factors associated with COVID-19 severity among Brazilian pregnant adolescents: a population-based study